2022
DOI: 10.3390/infrastructures7040058
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Shear Behavior of Stiffened Thin Steel Plate Shear Walls by New Welding Process

Abstract: Steel plate shear walls (SPSW) structures have been widely employed in multistory residential buildings. The traditional welding process may lead to serious welding deformation due to the thinness of the plate. In this study, a new welding process is proposed to ensure that the stiffeners and SPSWs bend as a whole, and the number of welds is reduced from 3 to 2. This process has better integrity than the traditional process owing to less welding residual stress and deformation. On the basis of low-cycle recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Either simple or moment-resisting beam-to-column connections can be used in this system [1]. The effect of connection on the behavior of the system was investigated by Kashan [2] and Xu [3].…”
Section: Introductionmentioning
confidence: 99%
“…Either simple or moment-resisting beam-to-column connections can be used in this system [1]. The effect of connection on the behavior of the system was investigated by Kashan [2] and Xu [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated the advantages of the use of these systems in significantly space-constrained areas and high seismic conditions [1][2][3]. Recent investigations allocated to improve the performance of this system, by limiting the interconnection interactions between the plate and the boundary elements [4,5], temperature field reconstruction [6], stiffened SPSWs [7,8], various geometrical shapes and infill plate conditions [9], effects of openings [10,11], infill plate types such as corrugated infill plates [12][13][14], and interconnection ratio [15,16], were studied to overcome previously reported structural issues such as excessive demands on columns, detrimental impacts of openings on SPSWs, problems in the buckling of infill plates, and so on.…”
Section: Introductionmentioning
confidence: 99%